Intercultural training of teachers and educators - Fiorucci, Massimiliano (Formazione & insegnamento, 2015)
After drawing an updated overview of the presence of immigrants in the Italian society and of non-national students in the school system, the contribution focuses on the issue of intercultural training of teachers and educators with particular reference to continuing education. The contribution, therefore, describes some of the main intercultural strategies for teachers training.